POSISI ISLAM DALAM SEJARAH PEMERINTAHAN NEGERI ADAT DI PULAU AMBON - Husen Assagaf (IAIN Ambon, 2018)
Ambon island is a portrait of the kings of the earth consisting of various state indigenous village. Indigenous village history, born from the origins of the state, known as the old country in the mountains and then molded in a safe/hena, soa, and uli, as a forerunner to the establisment of state indigenous village on the island of Ambon